Surface deformation and magma intrusion along divergent plate boundaries - Trippanera, Daniele (Università degli studi Roma Tre, 2015)
The interest in the role of magma in splitting plates at divergent plate boundaries has been recently re-enhanced. However, the peculiar mechanism by which the magma affects the geometry, the kinematics, and the temporal evolution of a rift is still poorly understood, especially in a long time perspective. Moreover, it is also necessary to better define how and to what extend the regional tectonics - by means of plate pull mechanism - affects the rift structures formation along these margins. The aim of this work is to address these issues through field survey and analogue modeling. Field survey consists of studying the surface deformation along different fissural portions of the magmatic systems at the Neovolcanic Zone of Iceland and the Main Ethiopian Rift, focusing mainly on: 1) single eruptive fissures (Laki, Eldgjá and Bardarbunga in Iceland) or narrow fissure zones hosting recent eruptive fissures (i.e., Sveinagjá and Sveinar in Iceland), 2) wider fissure zones where several rifting episodes occurred (i.e. Krafla, Vogar and Thingvellir in Iceland and Fantale in Ethiopia). In all these areas, fault and extension fracture geometries and kinematics have been systematically characterized, including the analysis of the structure of the fault’s lateral terminations, conceived as possible indicators of their propagation direction. In addition, these data have been integrated with the study of the roots (paleo-depth of about 1.5 km) of the fossil Alftafjordur magmatic system (Eastern Iceland). Analogue models have been used to test the effect of repeated dike intrusions at the surface, characterizing the geometry and the kinematics of dike-induced structures. In order to quantify and reconstruct the temporal evolution of the surface deformation, laser-scanner and Particle Image Velocimetry (PIV) techniques have been applied to the models. Field analysis show that at the surface, the eruptive fissures are bounded by normal faults forming a graben, thus suggesting a clear relationship between diking and surface deformation. Grabens, normal faults and extension fractures also characterize the surface of wider fissure zones. The faults usually exhibit an open structure, with locally tilted hanging wall and possible contraction at its base. However, the study of the fissure zones roots reveals that at depth the extension is accommodated by dikes, with almost no faulting. Analogue models results show that a graben forms above a dike complex gradually thickening at depth, whose structures geometry and kinematic depend on ratio between the intrusion depth and its cumulative thickness. This suggests, again, that diking may play a fundamental role in rift formation. Models and nature share several common features (i.e., graben with downward propagating normal faults, contraction at the base of the tilted hanging wall, subsidence above the dike complex and uplift to its sides), suggesting that most deformation along divergent plate boundaries may be acquired through repeated dike injection, requiring no direct tectonic contribution. However, the extension due to the regional tectonics remains still important for the long-term evolution of a divergent plate boundary: on one hand, it provides the required conditions for the rise and focusing of magma along the axial zone of the margin, on the other, it enhances the fault activity in more distal areas from the axial zones and during the inter-rifting periods.